ABOUT THE TYPES OF HOMOGENEOUS LINEAR DIFFERENTIAL EQUATIONS OF SECOND ORDER AND THEIR SOLUTIONS - Dimov, Lazo (Matematichki Bilten, 2016)
In the paper, types of linear differential equations of second order are defined in the sense of the known classification of the types of linear partial differential equations of second order. Then the shapes of their solutions are examined and some classes differential equations are solved.